2010
DOI: 10.1007/s00424-010-0798-0
|View full text |Cite
|
Sign up to set email alerts
|

Possible mechanisms of sudden cardiac death in top athletes: a basic cardiac electrophysiological point of view

Abstract: Sudden death among athletes is very rare (1:50,000-1:100,000 annually) but it is still 2-4 times more frequent than in the age-matched control population and attracts significant media attention. We propose a mechanism underlying sudden cardiac death in athletes that does not relate to myocardial ischemia but is based on repolarization abnormalities due to potassium channel downregulation and can also be best explained by the concurrent presence of several factors such as cardiac hypertrophy (athlete's heart),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 54 publications
(58 reference statements)
0
36
1
1
Order By: Relevance
“…Furthermore and even more importantly use of all these alkaloids may have additive effects further increasing the possibility of proarrhythmic risk and cardiac sudden death during administration of drugs effecting the cardiac repolarization or in certain pathophysiological conditions where repolarization reserve is impaired (including cardiac hypertrophy, hypertrophic cardiomyopathy, increased sympathetic tone, genetic defects, diabetes mellitus, renal failure, hypokalemia, hypothyroidism, etc.) [21,22]. In conclusion, the internal use of C. majus extracts or its alkaloids, berberine, chelidonine and especially sanguinarine in some situations where cardiac repolarization reserve is weak may increase the risk of potentially fatal ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore and even more importantly use of all these alkaloids may have additive effects further increasing the possibility of proarrhythmic risk and cardiac sudden death during administration of drugs effecting the cardiac repolarization or in certain pathophysiological conditions where repolarization reserve is impaired (including cardiac hypertrophy, hypertrophic cardiomyopathy, increased sympathetic tone, genetic defects, diabetes mellitus, renal failure, hypokalemia, hypothyroidism, etc.) [21,22]. In conclusion, the internal use of C. majus extracts or its alkaloids, berberine, chelidonine and especially sanguinarine in some situations where cardiac repolarization reserve is weak may increase the risk of potentially fatal ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Pedometers have been displayed in numerous studies to improve PA levels and are relatively inexpensive in addition to providing instantaneous output measures that are easily analysed by those with low literacy rates [31]. Average improvements over varying time periods up to and including 20 weeks has been calculated at 2,000 steps per day compared to control [32,33].…”
Section: Pedometersmentioning
confidence: 99%
“…Corrado et al [43] found that the relative risk of SCD was 2-4 in young athletes compared to inactive controls. SCD predominantly occurs during periods of medium-low oxygen demand such as during the warm up and inactive periods of matches [31]. Despite the severity of SCD, there is still great debate about the complex aetiological pathways involved [48,49] and the definition of SCD varies between studies [50].…”
Section: Risks Associated With Increasing Physical Activity Levels Sumentioning
confidence: 99%
“…Intensive research of HRV as a marker of cardiac autonomic function has been carried out in the past few decades [2][3][4]. HRV has been utilized to characterize adverse cardiovascular adaptation in certain disease entities such as ischemic heart disease and heart failure [5,6].…”
Section: Introductionmentioning
confidence: 99%